2023
DOI: 10.3389/fpls.2023.1211758
|View full text |Cite
|
Sign up to set email alerts
|

Impact of conservation tillage on wheat performance and its microbiome

Ida Romano,
Natacha Bodenhausen,
Gottlieb Basch
et al.

Abstract: Winter wheat is an important cereal consumed worldwide. However, current management practices involving chemical fertilizers, irrigation, and intensive tillage may have negative impacts on the environment. Conservation agriculture is often presented as a sustainable alternative to maintain wheat production, favoring the beneficial microbiome. Here, we evaluated the impact of different water regimes (rainfed and irrigated), fertilization levels (half and full fertilization), and tillage practices (occasional ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 117 publications
(203 reference statements)
1
3
0
Order By: Relevance
“…In our study, tillage practice was the main factor affecting the microbiome in the RA soil and RH (Table 4 ), indicating that the complete plant–microorganism–soil system was affected. These observations are in line with results from previous studies investigating wheat soils (Sommermann et al 2018 , Babin et al 2019 , Romano et al 2023 ), which highlights the stable legacy of tillage practice likely caused by differences in physical soil properties (Schlüter et al 2018 ) as well as differences in chemical composition (e.g. C and N stocks; Table S15 , Supporting Information ).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, tillage practice was the main factor affecting the microbiome in the RA soil and RH (Table 4 ), indicating that the complete plant–microorganism–soil system was affected. These observations are in line with results from previous studies investigating wheat soils (Sommermann et al 2018 , Babin et al 2019 , Romano et al 2023 ), which highlights the stable legacy of tillage practice likely caused by differences in physical soil properties (Schlüter et al 2018 ) as well as differences in chemical composition (e.g. C and N stocks; Table S15 , Supporting Information ).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Xu et al. (2020) observed that microbial community composition was affected by changes in water availability, showing that drought generally led to a decline in microbial biomass, while enhanced irrigation resulted in an increase, which might further translate into changes in microbial community composition ( Romano et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al (2016) observed that irrigation practices had a stronger effect on the abundance, diversity, and structure of bacterial communities than fertilization, confirming the driving effect of soil moisture on shift of bacterial communities. Recently, Xu et al (2020) observed that microbial community composition was affected by changes in water availability, showing that drought generally led to a decline in microbial biomass, while enhanced irrigation resulted in an increase, which might further translate into changes in microbial community composition (Romano et al, 2023).…”
Section: Simultaneous Application Of Trichoderma and Azotobacter Enha...mentioning
confidence: 99%
“…Several management elements, such as soil management techniques like tillage and soil cover, can impact the productivity and sustainability of rice-sweet corn systems in this region. The impact of various tillage regimes on crop performance and soil characteristics in diverse agricultural systems worldwide has been the subject of numerous researches [ [10] , [11] , [12] , [13] ]. Traditional methods like conventional tillage (CT), which include heavy mechanical soil disturbance via ploughing and harrowing, have been identified as contributing factors to soil deterioration, including decreased soil organic carbon (SOC) content, increased soil erosion, and lower fertility [ [14] , [15] , [16] , [17] , [18] ].…”
Section: Introductionmentioning
confidence: 99%